Copper Intercalation into Graphite - (:unkn) unknown (My University, 2012)
An electric brush is necessary for an electric motor to function. The purpose of this thesis is to propose a technique to improve electric brush properties in an effort to produce a more proficient electric motor by creating a new brush material with improved properties and performance. There are many applications for electric motors and each application would benefit from overall, increased proficiency. Understanding the role an electric brush plays within an electric motor is crucial to improving functionality. The proposed technique to create a novel graphite-copper material involves a two-step procedure that will intercalate CuCl2 into the graphite structure, and then by chemical reduction, will reduce the CuCl2 and result in the final products of copper and graphite. The proposed technique seeks to successfully increase the conductivity and wear properties of an electric brush by incorporating copper into graphite which will also enhance the properties of an electric motor. This thesis will detail the procedures of data collection and how to analyze results of the proposed technique. Expected results will also be discussed utilizing preliminary data collected utilizing XRD, SEM, TGA, and BET equipment. Finally, struggles and challenges of such a technique will also be discussed as well as plans for future work on the proposed technique.
Keywords: Copper; Graphite; Intercalation